2016
DOI: 10.1186/s12284-015-0073-2
|View full text |Cite
|
Sign up to set email alerts
|

Rice Improvement Through Genome-Based Functional Analysis and Molecular Breeding in India

Abstract: Rice is one of the main pillars of food security in India. Its improvement for higher yield in sustainable agriculture system is also vital to provide energy and nutritional needs of growing world population, expected to reach more than 9 billion by 2050. The high quality genome sequence of rice has provided a rich resource to mine information about diversity of genes and alleles which can contribute to improvement of useful agronomic traits. Defining the function of each gene and regulatory element of rice re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(72 citation statements)
references
References 232 publications
(195 reference statements)
2
70
0
Order By: Relevance
“…Online tools and publicly available databases are a convenient source to analyze our genes or conditions of interest (Agarwal et al, 2014); and much work has been done in rice with the aim to understand and improve its yield and stability (Agarwal et al, 2016). Out of 151 genes encoding NAC TFs in rice (Nuruzzaman et al, 2010), we found nine genes [ ONAC020 ( LOC_Os01g01470 ), ONAC026 ( LOC_Os01g29840 ), ONAC023 ( LOC_Os02g12310 ), ONAC055 ( LOC_Os03g01870 ), ONAC096 ( LOC_Os07g04560 ), ONAC025 ( LOC_Os11g31330 ), ONAC127 ( LOC_Os11g31340 ), ONAC128 ( LOC_Os11g31360 ), and ONAC129 ( LOC_Os11g31380 )] to be expressing in a seed-specific manner (Supplementary Figure S1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Online tools and publicly available databases are a convenient source to analyze our genes or conditions of interest (Agarwal et al, 2014); and much work has been done in rice with the aim to understand and improve its yield and stability (Agarwal et al, 2016). Out of 151 genes encoding NAC TFs in rice (Nuruzzaman et al, 2010), we found nine genes [ ONAC020 ( LOC_Os01g01470 ), ONAC026 ( LOC_Os01g29840 ), ONAC023 ( LOC_Os02g12310 ), ONAC055 ( LOC_Os03g01870 ), ONAC096 ( LOC_Os07g04560 ), ONAC025 ( LOC_Os11g31330 ), ONAC127 ( LOC_Os11g31340 ), ONAC128 ( LOC_Os11g31360 ), and ONAC129 ( LOC_Os11g31380 )] to be expressing in a seed-specific manner (Supplementary Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…Hence, NACs are an important class of TFs controlling various aspects of seed development (Agarwal et al, 2011) and their functions and sequences need to be explored further. A number of studies have successfully demonstrated the efficiency of a combinatorial strategy which combines high-resolution SNP-based and candidate gene-based association analysis, traditional genetic/QTL mapping, differential expression profiling and molecular haplotyping, for quantitative dissection of complex yield component traits in diverse crop plants, including rice (Zhao et al, 2011; Zuo and Li, 2014; Kujur et al, 2015a; Agarwal et al, 2016). It would be interesting to utilize this integrated approach to identify the functional alleles of NAC genes regulating grain size/weight variation, in cultivars adapted to diverse natural agro-climatic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…With the structural genomics projects well established, rice is now well supported by a wealth of genomic resources such as resequencing data of 3000 rice genotypes 4 , high throughput genotyping arrays [5][6][7] and expression arrays 8 . However, it was realized as early as 2004 by the rice research community that the greater challenge is to unravel the function of the sequence-based predicted genes in the rice genome 9 .…”
Section: Structural To Functional Genomicsmentioning
confidence: 99%
“…[4,5] NAC proteins evolved long before the emergence of land plants. [9][10][11][12][13][14][15][16] NAC TFs are greatly amplified in the plant lineage, constituting 151 protein encoding genes in rice, 117 in Arabidopsis, 152 in maize, and similar numbers in other species. [6][7][8] Members of this family play important roles in plant life, from embryogenesis till senescence.…”
Section: Introductionmentioning
confidence: 99%